Geographical patterns and determinants in plant reproductive phenology duration - Wang, Xinyang; Morin, Xavier; Zhang, Jian; Chen, Guoke; Mao, Lingfeng; Chen, Yuheng; Song, Zhuqiu; Du, Yanjun; Ma, Keping (Frontiers in Plant Science, 2023)
Biodiversity is and always has been an important issue in ecological research. Biodiversity can reflect niche partitioning among species at several spatial and temporal scales, and is generally highest in the tropics. One theory to explain it is that low-latitude tropical ecosystems are dominated by species that are generally only distributed over a narrow area. This principle, is known as Rapoport’s Rule. One previously unconsidered extension of Rapoport’s Rule may be reproductive phenology – where variation in flowering and fruiting length may reflect a temporal range. Herein, we collected reproductive phenology data for more than 20,000 species covering almost all angiosperm species in China. We used a random forest model to quantify the relative role of seven environmental factors on the duration of reproductive phenology. Our results showed that the duration of reproductive phenology decreased with latitude, though there was no obvious change across longitudes. Latitude explained more of the variation in the duration of flowering and fruiting phases in woody plants than in herbaceous plants. Mean annual temperature and the length of the growing season strongly influenced the phenology of herbaceous plants, and average winter temperature and temperature seasonality were important drivers of woody plant phenology. Our result suggests the flowering period of woody plants is sensitive to temperature seasonality, while it does not influence herbaceous plants. By extending Rapoport’s rule to consider the distribution of species in time as well as space, we have provided a novel insight into the mechanisms maintaining high levels of diversity in low-latitude forests.